MAKROFAG PADA JARINGAN ADIPOSA OBES SEBAGAI PENANDA TERJADINYA RESISTENSI INSULIN - Mukhtar, Diniwati (MAJALAH ILMIAH WIDYA, 2012)
Obesity has become an epidemic affecting developed and developing countries. Along with the increase in obesity is a parallelincrease in the prevalence of type 2 diabetes, impaired glucose tolerance, and other complications of obesity, such as hypertension.The focus this review is on the role of macrophage in adipose tissue as a marker of insulin resistance in obesity. Insulin resistanceis a central player of obesity related metabolic derangements. An increased number of macrophages resident in human adiposetissue has been reported in obesity. During adipose tissue expansion, hypoxia can occur due to reduced delivery of oxygen to thehypertrophic adipocytes. This hypoxia can cause adipocyte cell death and macrophages can be attracted to adipose tissue tophagocytose these dead adipocytes. The macrophages in adipose tissue are localized around dead adipocytes and form typicalcrown-like structures. Macrophage chemoattractant protein-1 (MCP-1) is a well-known regulator of macrophage recruitment to siteof inflammation. In obesity show increased plasma levels of MCP-1. Exercise has been shown to improve insulin sensitivity in obeseindividuals even in the absence of weight loss. Conclusion: overexpression MCP-1 in human obese was associated with insulinresistance. Exercise training reduced peripheral markers of inflammation, among them MCP-1.